Discurso e identidade sociocultural Parintinense - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This paper aims to reflect on the discursive constitution of the identity sociocultural of Parintins people. The qualitative research was conducted through semi-structured interviews, audio-recorded and later transcribed, from which was formed the corpus. The interviews were made in the city of Parintins, more precisely in the Historic Center, with a group of people over 70 to 79 years old. It was undertaken a search for answers to the question: which way, discursive formations and interdiscourse are present in the narrative of Parintins people on their identity sociocultural? The analysis sought to know how sociocultural processes contribute to constitution of meanings about Parintins people, from which discursive and interdiscourse formations they are coming, taking into account the life experience of the group interviewed and the city history. The perspective obtained from Discourse Analysis of Michel Pêcheux and Eni Orlandi guided this study, which relates language, history and ideology in the production of meaning. The Parintins identity are addressed with the support of the theories from Tomaz Tadeu da Silva, Bauman, Kathryn Woodward, Stuart Hall, Cush and Goffman. Already known and widely publicized senses about the Parintins people identity were confirmed. However others, that suggest resistance to those of a single identity, predominate in the subjects' discourses, giving birth to the inhabitants' view of what binds them ideologically to the city, to culture, to history, in other words, what in the moment, makes them Parintins people.
Keywords: Formação ideológica; Formação discursiva; Interdiscurso; Identidade Sociocultural; CIÊNCIAS HUMANAS